A STUDY ON THE INCIDENCE OF NEEDLE STICK INJURY (NSI), ASSOCIATED DEMOGRAPHIC FACTORS AND INJURY-RELATED CHARACTERISTICS AMONG NURSING STUDENTS OF SELECTED NURSING INSTITUTIONS OF AIZAWL, MIZORAM - Laldingliani Sailo; Malsawmdawngkimi .; R. Lalruatkimi; Lalremmawii Ralte; Mufeez Ur Rahman (EPRA International Journal of Multidisciplinary Research (IJMR), 2026)
Needle Stick Injury (NSI) is a significant occupational hazard for healthcare workers, especially nursing students during clinical training. Inadequate awareness of standard precautions and post-exposure protocols, like Post-Exposure Prophylaxis (PEP), heightens the risk of serious infections such as Hepatitis B, C, and HIV. This study aimed to assess the incidence of NSI among nursing students in Aizawl, Mizoram, and explore its association with academic year. A total of 830 nursing students participated in a quantitative survey utilizing a self-administered questionnaire. Results indicated that 29.6% of students reported experiencing at least one NSI, primarily caused by hollow-bore needles (61.4%), with recapping being the most common procedure leading to injuries (45.1%). Most incidents (71.1%) were single occurrences within the past year; however, neglect (47.0%) was the main reason for not reporting incidents, despite 74.8% of cases being reported to authorities. Common immediate measures taken post-exposure included washing the site with soap and water (66.2%). A statistically significant correlation was noted between academic year and NSI incidence (χ²=71.1, df=3, p